“Diseño de un Sistema de Costos por Órdenes de Producción para la casa Deportiva “DERMAY” del Cantón La Maná, Provincia de Cotopaxi” - Duarte Infante, Julissa Elizabeth (2020)
Taking into account that an adequate cost system provides a firm structure for decision making primarily to determine the real value of a product, good or service, it was considered important to propose the design of a cost system for production orders for the House Deportiva DERMAY, from the canton of The Manna, in the province of Cotopaxi, because it showed the absence of formats that allow keeping an adequate record of the costs generated in the production of sports equipment and other products that are made in this company handmade. Using for this purpose basic research, bibliographic research for the collection of theoretical information, field research for the diagnosis of the current situation through the interview and employee surveys. In addition, the inductive and analytical methods were used, having as an investigative instrument an open-ended questionnaire for the interview and multiple-choice questions for the surveys. Through the diagnosis of the DERMAY Sports House Company of the canton of The Manna, it was evidenced that it does not have a documented way with processes established for its production, therefore the description of the processes of elaboration of sportswear with their respective activities was made by flowcharts. The cost system was made up of an account plan. For the determination of the total cost and the sale price, a production lot of 45 sports teams was calculated that showed a favorable utility for the company.